The production on memory of productivity scholarship students in Information Science - Sá, Paloma Israely Barbosa; Bufrem, Leilah Santiago (Ciência da Informação em Revista, 2023)
Identifies the periodic scientific production provided by CNPq scholarship students on productivity, in categories 1 and 2, in the area of ​​Information Science (CI) in Brazil, in studies on Collective Memory and Social Memory. It characterizes the scientific research produced from a corpus of journal articles indexed in Brapci, from 1975 to 2019. According to the data obtained, it is possible to conclude that the number of CNPq scholarship students who conduct researches on Productivity is incipient, as well as the production these students provide. Although less than half of the articles analyzed define collective and social memory, it concludes that there is room for discussion from the visible theoretical maturation present in discussions on conceptualization of memory.